The disfigured face : traditional natural law and its encounter with modernity - Cortest, Luis (Moral philosophy and moral theology., 2008)
Luis Cortest shows how traditional natural law was transformed by thinkers like Locke and Kant into a doctrine compatible with early modern notions of nature and morality. One of the first great debates about moral philosophy took place in 16th-century Spain, as a dispute concerning the humanity of Native Americans.